'House of mirrors': The sentient house as homosocial space in Andrew Pyper's The Guardians. Issue 1 (1st April 2017) - Mayr, Suzette
In The Poetics of Space ([1958] 1969), Gaston Bachelard proposes that 'The house is a "psychic state"', and focuses on the childhood house – specifically 'the house we were born in' – because he believes that with this 'first' house one establishes a 'passionate liaison'. Andrew Pyper's novel The Guardians (2011) is ostensibly a haunted house novel about four men battling a malevolent house, but the novel is also about the unique love the men express for and with each other – what masculinity scholars Hammarén and Johansson would label 'horizontal homosociality' or 'a more sensitive and intimate masculinity'. Ultimately, the malevolent house provides the only venue in which the men can express this intimate love for each other. I argue that the house's relationship with the men is, fundamentally, a 'passionate liaison'; for while the men were not born in the house and so it is not literally their 'first' house, the house forces key rites of passage that bind the men and the house together forever. With the house's destruction at the novel's conclusion the male relationships are constrained and hollowed out by hegemonic masculine expectations and stereotypes.